ANALYSIS OF CONSUMER PERCEPTIONS OF SERVICE QUALITY OF DRINKING WATER COMPANIES - Athar, Handry Sudiarta; Sutanto, Himawan; Kusmayadi, Iwan (Dinasti Publisher, 2020)
The aim of the research was to analyze the service quality of drinking water companies using the servQual method. This research is a quantitative research with research method conducted in different companies in the city of Mataram, Lombok. Data analysis was performed using the service quality method (ServQual). The results showed that the customer satisfaction criteria on each service characteristic in general of the five components were on average very good, this is known from the results of the NKJ calculation which are results 1,022 that are classified as very good.